Understanding the reinforcing efficiency of waste eggshell‐derived nano calcium carbonate in natural rubber composites with maleated natural rubber as compatibilizer. Issue 7 (10th May 2019) - Roy, Kumarjyoti; Debnath, Subhas Chandra; Raengthon, Natthaphon; Potiyaraj, Pranut
Abstract : Calcium carbonate nanoparticles were synthesized from eggshell waste using ball mill treatment and characterized by Fourier transform infrared (FTIR), X‐ray diffraction (XRD), and field‐emission scanning electron microscopy (FESEM) analysis. Then, waste eggshell‐derived nano calcium carbonate (WESNCC) was used as filler to reinforce natural rubber (NR) composites with and without the presence of maleated natural rubber (MNR) as compatibilizer. MNR‐compatibilized NR/WESNCC composites showed remarkable enhancement in the torque difference, tensile, and thermal properties as compared to either uncompatibilized NR/WESNCC composites or unfilled NR system. Crosslinking degree measurements indicated excellent interfacial interaction between NR matrix and WESNCC in presence of MNR as compatibilizer. A probable mechanism is suggested to explain the interaction between NR matrix and WESNCC in the presence of MNR. This study provides unique way to develop WESNCC‐based rubber composites for future industrial and engineering application. POLYM. ENG. SCI., 59:1428–1436 2019. © 2019 Society of Plastics Engineers